Redox cycling-based immunoassay for detection of carcinogenic embryonic antigen - Lee, Ga-Yeon; Park, Jun-Hee; Chang, Young Wook; Cho, Sungbo; Kang, Min-Jung; Pyun, Jae-Chul (ELSEVIER SCIENCE BV, 2017)
Redox cycling based on an interdigitated electrode (IDE) was used as a highly sensitive immunoassay for carcinogenic embryonic antigen (CEA) through the quantification of 3,3',5,5'-tetramethylbenzidine (TMB). For the redox cycling process, one pair of interdigitated finger electrodes was used as the first working electrode (generator) for cyclic voltammetry of TMB, and another pair of interdigitated finger electrodes was used as the second working electrode (collector) for sequential application of potentials for reduction and oxidation of TMB. The reduction (and oxidation) products of TMB at the collector were supplied to the generator, and following sequential oxidization (and reduction) at the generator, again supplied to the collector. Such redox recycling processes between the generator and collector allowed signal amplification. In this work, the influences of the following factors on the redox cycling of TMB were analyzed: (1) the redox potential at the collector, (2) the gap between the interdigitated finger electrodes, and (3) the scan rate of the generator. The redox potential and electrode gap influences were simulated with COMSOL software and compared with empirical results. At the optimum redox potentials and electrode gap, redox cycling was estimated to be five-fold more sensitive for the quantification of TMB than conventional cyclic voltammetry using one pair of interdigitated finger electrodes as the working electrode. Finally, redox cycling was applied to a commercial immunoassay for CEA, and the sensitivity of redox cycling was three-fold higher than that of conventional cyclic voltammetry using a single set of interdigitated finger electrodes as the working electrode. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: INTERDIGITATED ARRAY ELECTRODES; ELECTROCHEMICAL ELISA; NANOELECTRODE ARRAYS; IDA ELECTRODES; FABRICATION; BIOSENSOR; MICROELECTRODE; PEROXIDASE; SIMULATION; EFFICIENCY